Photocatalytic Degradation of Recalcitrant POME Waste by using Silver Doped Titania: Photokinetics and Scavenging Studies - Ng, Kim Hoong; Lee, Chea Hui; Khan, Maksudur R.; Cheng, C. K. (Elsevier, 2016)
The current paper reports on the photo-degradation of palm oil mill effluent over silver-modified titania (Ag/TiO2) under visible light irradiation. TiO2-based photocatalysts with 0.25–5.0 wt% of Ag metal loadings were prepared by impregnating TiO2 with chemically-reduced Ag nanoparticles from the AgNO3 solution. The XRD characterization suggests that anatase was the predominant phase for all the as-synthesized photocatalysts. In addition, UV–Vis DRS confirmed that the Ag inclusion has extended the absorbance of photocatalysts to the visible light region. Moreover, the band gap energy of TiO2 was successively reduced to 2.69 eV (5.0 wt% Ag/TiO2), a drop from 3.1 eV (bare TiO2). Consequently, the POME degradation efficiency jumped 300–15.03% by photoreaction over 1.0 g/L of 0.25 wt% Ag/TiO2 compared to the bare TiO2. The optimum loading of Ag was found to be 0.5 wt%, with corresponding degradation of 19.73%, and can be enhanced further to 26.77% with the optimum catalyst loading of 1.5 g/L. Moreover, scavenging study confirmed that the primary reactive species for POME degradation in the current system was OHradical dot free radicals. In recycling test, the degradation efficiency of 0.5 wt% Ag/TiO2 dropped to 11% and 13% for second and third cycle, respectively, due to leaching of Ag metal as proven by ICP-MS, post-reaction.